2020
DOI: 10.1007/s13187-020-01860-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Colon Cancer Prevention in Poland. A Long Way Off

Abstract: The aim of this study was to analyse knowledge on colon cancer prevention among patients of primary care and identify their sources of information. The questionnaire study was conducted among patients of 36 primary healthcare clinics in Poland between September 2018 and February 2019. Patients were interviewed separately by trained researchers. Over 39% of the primary health patients declared that their knowledge about colon cancer prevention is unsatisfactory. Information about colon cancer prevention varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Importantly, the incidence and mortality of preventable cancers are higher in men than in women ( 1 , 4 ). Our results also contradict previous findings that cancer prevention counselling intensifies with the growing age of patients ( 65 ).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Importantly, the incidence and mortality of preventable cancers are higher in men than in women ( 1 , 4 ). Our results also contradict previous findings that cancer prevention counselling intensifies with the growing age of patients ( 65 ).…”
Section: Discussioncontrasting
confidence: 82%
“…Preventive counselling is often neglected by health care providers ( 32 , 64 , 65 ). It has been shown that more than 60% of Polish general practitioners (GPs) do not assess patients' lifestyles during consultations, although 64% believe they are obliged to provide health education; only 30% of GPs think that their knowledge in this area is sufficient ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were found by Patelarou et al (2021), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020;Obiała et al, 2020;Patelarou et al, 2021). Skeptics also use online platforms to advocate vaccine refusal.…”
Section: Role Of Trust In Information Sources In Vaccination Behaviormentioning
confidence: 99%